1992
DOI: 10.1007/bf00174480
|View full text |Cite
|
Sign up to set email alerts
|

Continuous culture of the hyperthermophilic archaeum Pyrococcus furiosus

Abstract: A system for continuous culture of the hyperthermophilic archaeum Pyrococcus furiosus in the absence of elemental sulphur has been developed. An all-glass "gas-lift" bioreactor was used to provide high mass transfer at low shear forces, whilst eliminating the potential for corrosion. Steady-state cell densities of P.furiosus were found to increase with higher inert gas flow rates, reaching a maximum in this system with 0.5 vol. v o l -1 m i n -1 of nitrogen (N2). N2 permitted higher cell densities than the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…Continuous culture experiments (pH 7.0 at 90°C) were carried out in the apparatus described previously [2], except that the vessel temperature was controlled directly by the output from a Haake F3 temperature controlled bath (Fisher Scientific). The mineral salts solution [2] was modified by the addition of 1 ml per l of solution D, which comprised 10 g l −1 iron(II) chloride tetrahydrate in 1 M HCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous culture experiments (pH 7.0 at 90°C) were carried out in the apparatus described previously [2], except that the vessel temperature was controlled directly by the output from a Haake F3 temperature controlled bath (Fisher Scientific). The mineral salts solution [2] was modified by the addition of 1 ml per l of solution D, which comprised 10 g l −1 iron(II) chloride tetrahydrate in 1 M HCl.…”
Section: Methodsmentioning
confidence: 99%
“…The initial isolation showed that the organism was able to grow both proteolytically on peptone and saccharolytically on maltose or starch in the presence of yeast extract [1]. We have previously shown that a glass gaslift bioreactor can be used to grow the organism at high cell densities in the absence of elemental sulfur [2]. A complex medium containing peptone and yeast extract was used in continuous culture.…”
Section: Introductionmentioning
confidence: 99%
“…To improve biomass yield of the hyperthermophilic archaeon Pyrococcus furiosus, Raven et al (1992) used continuous cultures with defined and minimal media and achieved a maximal cell density of 10 8 cells ml -1 when P. furiosus was grown on starch (Raven and Sharp 1997). Rinker et al (1999) cultivated the hyperthermophilic heterotrophs Metallosphera sedula, P. furiosus and Thermococcus litoralis in a chemostat (Table 2) and observed the production of exopolysaccharides.…”
Section: Innovative Fermentation Processes For the Production Of Archmentioning
confidence: 99%
“…I? furiosus was grown in a continuous culture on a medium containing maltose (5 g/l), peptone (1 g/l) and yeast extract (1 g/l) as carbon and energy sources (Raven et al, 1992).…”
Section: Purification Of Acetyl-coa Synthetase (Adp-forming)mentioning
confidence: 99%